Comparative Outcomes of Traditional Versus High-Definition Liposuction in the Surgical Management of Gynecomastia: A Prospective Study: Traditional Versus High-Definition Liposuction in the Surgical Management of Gynecomastia - Bilal, Muhammad; Yousaf, Muhammad Amin; Khalid, Kamran; Khalid, Farrukh Aslam; Rabbani, Ammara; Bashir, Barira; Ahmad, Junaid (Pakistan Journal of Health Sciences, 2026)
The prevalence of male patients seeking surgical treatment for gynecomastia has increased in recent years. While traditional liposuction with or without gland excision remains a standard approach, high-definition (HD) liposuction has emerged as a technique that offers improved aesthetic outcomes through enhanced chest contouring. Objectives: To compare the early and late clinical outcomes of traditional liposuction versus high-definition liposuction in the surgical management of gynecomastia. Methods: This prospective, comparative study was conducted at Jinnah Burn Reconstruction Surgery Centre, Allama Iqbal Medical College, Lahore. Sixty patients aged 18–55 years were enrolled and divided into two groups: Group A (traditional liposuction) and Group B (high-definition liposuction). Results: In this study, the mean age of the cases was 25.33 ± 4.14 in Group A, while 26.63 ± 3.88 in Group B. The mean operation time was 86.33 ± 18.38 in Group A, while 52.60 ± 25.75 in Group B, with a statistically significant p=0.001. Patient satisfaction after 3 months (86.7% vs 96.7%, p-value=0.161) and 1 year (66.7% vs 93.3%, p-value<0.001) was higher in Group B. The comparison of seroma, infection, and asymmetry showed insignificant differences p-value > 0.005. Conclusions: High-definition liposuction appears to offer superior aesthetic results and greater patient satisfaction compared to traditional liposuction, without an increase in complications. It represents an effective alternative in the surgical management of gynecomastia.